FACTORS AFFECTING FARMERS’ ACCEPTABILITY TOWARD AGRICULTURAL INSURANCE PROGRAM IN MALANG, EAST JAVA, INDONESIA - Sujarwo Sujarwo (Agricultural Socio-Economics Journal, 2017)
Farmers face high risk and uncertainty in their production. There are farmers that are able to manage the risk; however, most of them fail to adapt the risk and uncertainty. If catastropihic losses happen then the farmers will suffer and come to the poverty. Therefore, government of Indonesia attempts to conduct agricultural insurance policy to prevent that case happening specially for small-scale farming. This study contributes in understanding what factors will endorse the acceptance of agricultural insurance for small-scale farming. The data analysis employed is binomial logistic regression in finding factors that negatively or positively affect the agricultural insurance program. The data was obtained through survey conducted in January to Mei 2017. The location of this study is Malang Regency, East-Java Province, Indonesia. The results found that there was 50 percent of the farmers accepting the agricultural insurance program and the other half of farmers unwilling to support the program. Regarding factors which affect negatively to the willingness to accept agricultural insurance are age, profit, and the number sources of income. Then, the factors which affects positively to the agricultural insurance are farming size, the experience of buying insurance, and also the intencity of farmers in attending farmers’ group meeting.